2021
DOI: 10.1093/conphys/coaa135
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones in Pacific walrus bones collected over three millennia indicate physiological responses to changes in estimated population size and the environment

Abstract: The Pacific walrus (Odobenus rosmarus divergens) is an iconic Arctic marine mammal and an important resource to many Alaska Natives. A decrease in sea ice habitat and unknown population numbers has led to concern of the long-term future health of the walrus population. There is currently no clear understanding of how walrus physiology might be affected by a changing Arctic ecosystem. In this study, steroid hormone concentrations (progesterone, testosterone, cortisol and estradiol) were analysed in walrus bones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…While biologically relevant patterns of trace elements and stable isotopes have been measured in opercula of teleost species (Tzadik et al 2017), no lipophilic steroid hormones measurements, to date, have been reported from these hard parts. However, teleost bones contain considerable amount of lipid (Toppe et al 2007) and lipophilic steroid hormones (progesterone, testosterone, estradiol, and cortisol) have been measured in marine mammal cortical bone buried for thousands of years, lending evidence that bone is a long-term reservoir of biologically relevant steroid hormones (Charapata et al 2018(Charapata et al , 2021. Potentially, lipophilic steroid hormones are deposited in annual growth increments of teleost opercula through time, similar to findings of various mammalian vertebrates (Trumble et al 2013).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…While biologically relevant patterns of trace elements and stable isotopes have been measured in opercula of teleost species (Tzadik et al 2017), no lipophilic steroid hormones measurements, to date, have been reported from these hard parts. However, teleost bones contain considerable amount of lipid (Toppe et al 2007) and lipophilic steroid hormones (progesterone, testosterone, estradiol, and cortisol) have been measured in marine mammal cortical bone buried for thousands of years, lending evidence that bone is a long-term reservoir of biologically relevant steroid hormones (Charapata et al 2018(Charapata et al , 2021. Potentially, lipophilic steroid hormones are deposited in annual growth increments of teleost opercula through time, similar to findings of various mammalian vertebrates (Trumble et al 2013).…”
Section: Introductionmentioning
confidence: 85%
“…To correct these errors, samples estimated at >100 % lipid were assigned a standardized 90% lipid value, while total error in measurement (negative lipid mass extracted) was assigned the mean percent lipid from all other growth increments for each individual fish. These lipid correction factors (90% and mean percent lipid) were multiplied to individual GI masses to retain a relative individualized lipid mass per sample (Charapata et al 2018(Charapata et al , 2021. Samples were reconstituted with 1.25 mL of methanol, transferred into another 2 mL microvial, and stored at -80 C until steroid hormone could be measured.…”
Section: Steroid Hormone Extraction and Measurementmentioning
confidence: 99%
“…The loss of sea ice could impact the females’ ability to successfully reproduce and provide adequate nutrition for their offspring [ 12 , 36 , 86 ]. Stress and reproductive biomarkers analyzed from recent and archaeological Pacific walrus bones suggested potential resilience to declining sea ice [ 91 ], but ongoing monitoring of this species is necessary to track their response to unprecedented change.…”
Section: Discussionmentioning
confidence: 99%